(untitled) (Annals of Medical Research, 2021)
Aim: Paratricipital approach and Olecranon osteotomy are most commonly used to treat intra-articular distal humerus fractures in adults. In this study we have analysed the patients in whom we performed open reduction and internal fixation with and without olecranon osteotomy and evaluated the advantages and disadvantages of both methods. Materials and Methods: Between 2014 and 2018, 36 adult patients with intra-articular distal humerus fracture were retrospectively analysed. According to AO classification system 9, patient has Type B2, 1 Type B3, 7 Type C1, 10 Type C2 and 9 Type C3 fractures. Mayo Elbow Performance Score for evaluation of the elbow joint stability and Disabilities of Arm, Shoulder and Hand score to evaluate the functionality of shoulder, arm and hand was used. Results: Paratricipital approach was used in 12 patients (8 male , 4 female) and olecranon osteotomy in 24 patients. Mayo Elbow Performance Score and Disabilities of Arm, Shoulder and Hand scores were found respectively 15.808 and 81.25 in the Paratricipital group whereas those values were determined as 17.37 and 79.17, respectively. No statistically significant difference was found between two groups in terms of these two scorings (p=0.147 and p=0.244, respectively) A statistically significant difference was detected between the groups in terms of heterotopic ossification ( p=0.008). In the paratricipital group; no heterotopic ossification was found in 7 (58.3%) patients whereas Type 1 heterotopic ossification was detected in 5 (41.7%) patients. In the olecranon osteotomy group; no heterotopic ossification was found in 4 (16.7%) patients whereas Type 1 and Type 2 heterotopic ossification were detected in 16 (66.7%) and 4 (17.7%) patients, respectively (p=0.008). A statistically significantly higher rate of elbow degeneration and heterotopic ossification was observed in the patients who underwent osteotomy compared with those who were not performed osteotomy (p=0.008) Conclusions: Paratricipital approach can be performed as an alternative treatment option in the distal humerus fractures to reduce the postoperative complications even though it does not allow to perform a comprehensive preoperative evaluation of the joint as well as olecranon osteotomy approach.